Glaucoma in general practice - B.N. Gundry (South African Family Practice)
Glaucoma is a silent condition very rarely presenting with headaches and only leading to decreased vision in the very advanced stages. Disc cupping and intraocular pressure measurement are important features in making the diagnosis. Acute angle closure is very rare and needs urgent referral. Most patients will be well controlled with medical therapy alone.